Towards Self-Reinforced PLA Composites for Fused Filament Fabrication - Neha Yadav; Tim Richter; Oliver Löschke; Bilen Emek Abali; Dietmar Auhl; Christina Völlmecke (Applied Sciences, 2023)
Aligned with the Sustainability Development Goals (SDGs), we present the complete methodology of preparing bio-based polymer filaments to be used in additive manufacturing, specifically by means of so-called Fused Filament Fabrication (FFF) in 3D printing. Filament production and 3D printing were both developed and optimised in this work. First, we focused on the steps of producing and optimising the extrusion process of unreinforced polylactic acid (PLA) composite filaments. Second, we studied the resulting material properties by discussing the selection of a specimen geometry and the international standards adequate for FFF 3D printing. Moreover, we investigated the process parameters in order to achieve reliable structures. Based on the reinforcement material (stereocomplex fibres (Sc-PLA fibre) and bi-component fibres (bi-co PLA fibre), base-matrices were selected for producing un-reinforced filaments. In this way, we present the complete preparation approach by identifying problems and pitfalls for fostering studies of bio-based polymer filaments.